2005
DOI: 10.1093/aob/mci200
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Carbohydrate and Nitrogen for the Resprouting Ability of Quercus crispula Seedlings

Abstract: These results suggest that carbohydrate storage has a stronger influence on resprouting in Quercus crispula than N storage. However, the size of the resprouting shoot was positively correlated with the amount of both N and TNC in roots. The level of N storage is, therefore, also important for the growth of resprouting shoots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 38 publications
4
37
1
2
Order By: Relevance
“…Some woody plants store enough carbohydrate reserves in stumps and roots to meet more than one resprouting event following a disturbance (Carpenter et al 2008;Luostarinen and Kauppi 2005). To recover after a browsing event which removes leaf material, a plant needs viable meristems and carbon reserves, at least until new shoots become functional and can photosynthesize (Kabeya and Sakai 2005). Resprouting trees also rely on stored carbohydrate reserves to support growth and respiration until sufficient leaf area has been regrown for carbon assimilation to meet growth demands (Chapin et al 1990;Bond and Midgley 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some woody plants store enough carbohydrate reserves in stumps and roots to meet more than one resprouting event following a disturbance (Carpenter et al 2008;Luostarinen and Kauppi 2005). To recover after a browsing event which removes leaf material, a plant needs viable meristems and carbon reserves, at least until new shoots become functional and can photosynthesize (Kabeya and Sakai 2005). Resprouting trees also rely on stored carbohydrate reserves to support growth and respiration until sufficient leaf area has been regrown for carbon assimilation to meet growth demands (Chapin et al 1990;Bond and Midgley 2001).…”
Section: Introductionmentioning
confidence: 99%
“…When photosynthetically efficient, a resprouting plant can reach peak growth and then allocate carbon towards storage (Kabeya and Sakai 2005). For example, Van der Heyden and Stock (1996) showed that after branch cutting, regrowth of the shrub Osteospermum sinuatum Norl.…”
Section: Introductionmentioning
confidence: 99%
“…A maior taxa inicial de crescimento da brotação, em comparação à de plantas estabelecidas a partir de mudas, se deve, principalmente, à presença de um sistema radicular já estabelecido, o que facilita a absorção de água e nutrientes e o uso de reservas orgânicas e inorgânicas, presentes na cepa ou nas raízes (Blake, 1983;Reis & Kimmins, 1986;Teixeira et al, 2002;Kabeya & Sakai, 2005;Walters et al, 2005). Reis & Kimmins (1986) observaram que, após decepa de plantas jovens de eucalipto que cresciam em vasos, o sistema radicular contribuiu com 75% do fósforo requerido para o crescimento dos brotos, em solo relativamente fértil, e 100%, em solo pouco fértil, 1,5 mês após decepa das plantas.…”
Section: Introductionunclassified
“…Greater or lesser concentrations of some nutrients in the regrowing tissues occurs as a result of increased metabolic activity linked with the capacity of translocated nutrients from subterranean organs to above ground plant parts [59,60], which was observed in managed rosewood plantations.…”
Section: Changes In Nutritional Status Associated With the Managementmentioning
confidence: 99%